Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Intensitas Aset Tetap dan Fasilitas Terhadap Manajemen Pajak dengan Indikator Tarif Pajak Efektif: The Effect of Profitability, Leverage, Company Size, Intensity of Fixed Assets and Facilities on Tax Management with Effective Tax Rates Indicators - Mutia Dianti Afifah; Mhd Hasymi (Universitas Muhammadiyah Sidoarjo, 2020)
This research aims to determine the effect of profitability, size, fixed asset intensity, and tax incentive to tax management using effective tax rates as an indicator. The data in this research obtained from the annual report of financial statements on manufacturing companies listed in the Indonesian Stock Exchange period 2011-2017. Sample selection method used purposive sampling method. Analytical techniques in this research used descriptive statistics, panel data regression, test classic assumptions and hypothesis testing. The total sample in this research are 48 companies. The result proves that profitability, size, tax incentive have a negative effect to tax management using effective tax rates as an indicator. Fix asset intensity has no effect to tax management using effective tax rates as an indicator.